MENINGKATKAN BAKAT DAN MINAT ESTETIKA MASYARAKAT DALAM BIDANG KETERAMPILAN DI MASA PANDEMI COVID-19 - Akhsan, Akhsan; Heril, Muhammad; Sapan, Wahyullah (Ekalaya: Jurnal Pengabdian Kepada Masyarakat Indonesia, 2022)
One of the problems that exist in Lunjen village is the lack of aesthetic and aesthetic values ​​at the MIS GUPPY RUMBIA school. One of the programs implemented in Lunjen village is school painting which is one of the areas of skill. The objectives of holding a painting work program at the MIS GUPPI RUMBIA school are: 1) to beautify the school environment. 2) build interest in attracting interest for children to go to school at MIS GUPPI RUMBIA. Community service in this article. The result of this work program is an increase in the aesthetic value of the school from the movement to care for the school environment as well as increasing interest in enrolling in schools, especially at MIS GUPPI RUMBIA